A critical review of ESP curriculum for pharmacists at SMKN 5 Pangkalpinang, Bangka Belitung - Pratiwi Amelia (UAD TEFL International Conference)
This paper presents a critical review of the ESP curriculum for the tenth grade of pharmacists’ students at SMKN 5 Pangkalpinang. This critical review is based on the theory of Language Curriculum Design proposed by Nation & Macalister (Nation & Macalister, 2007). It is found that the English curriculum, which uses by SMKN 5 Pangkalpinang is not suitable for the students of pharmacists. Teaching English for pharmacists at SMKN 5 Pangkalpinang needs modification and revitalisation to accommodate the needs of the students in the future. The general teaching materials for the students will not fulfil the language skills needed by the students. However, the materials should be specific. The revitalization of ESP curriculum at SMKN 5 Pangkalpinang should be based on research on the environment and need analysis of learning English as pharmacists. It also should consider the principles of curriculum design in teaching English for a specific purpose.